2006
DOI: 10.1002/pmic.200500845
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of sperm regions that mediate sperm-egg interactions

Abstract: The sperm interacts with three oocyte-associated structures during fertilization: the cumulus cell layer surrounding the oocyte, the egg extracellular matrix (the zona pellucida), and the oocyte plasma membrane. Each of these interactions is mediated by the sperm head, probably through proteins both on the sperm surface and within the acrosome, a specialized secretory granule. In this study, we have used subcellular fractionation in order to generate a proteome of the sperm head subcellular compartments that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 67 publications
3
98
0
1
Order By: Relevance
“…ZPBP1 has been reported to persist in acrosome-reacted sperm (31,51), and ZPBP1 is released by the A23187-induced acrosome reaction (42). To understand why more significant phenotypes are observed in spermatids and spermatozoa lacking ZPBP1 in addition to the more widespread intra-acrosomal localization of ZPBP1 compared to ZPBP2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ZPBP1 has been reported to persist in acrosome-reacted sperm (31,51), and ZPBP1 is released by the A23187-induced acrosome reaction (42). To understand why more significant phenotypes are observed in spermatids and spermatozoa lacking ZPBP1 in addition to the more widespread intra-acrosomal localization of ZPBP1 compared to ZPBP2 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent explosion of proteomics studies has identified many reproductive proteins in taxa ranging from crickets and honeybees to rodents and humans. (15,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) Applying mass spectrometry (MS)-based proteomics to the study of reproduction has been particularly fruitful, in our view, because reproductive tissues are often specialized cell types with the discrete function of producing proteins involved in a specific biological process. Thus, biochemical isolation and purification of proteins from these tissues and cell types are straightforward, and large amounts of relatively pure protein mixtures can be analyzed by MS.…”
Section: Identifying Reproductive Proteinsmentioning
confidence: 99%
“…Biochemical or physical fractionation, e.g., of mouse sperm heads (39) or abalone vitelline envelopes, (15,26) is a simple, powerful method of isolating reproductive structures to guide proteomic analysis to proteins that play direct reproductive roles.…”
Section: Identifying Reproductive Proteinsmentioning
confidence: 99%
“…In view of the recent suggestions of the potential role of RNA in early embryo developed, these could be an important surreptitious finding (Miller et al 2005). Stein et al (2006) performed a selected proteomic analysis of mouse sperm of the regions that are likely to be involved in mediating sperm-egg interactions. Subcellular fractionation included enrichment of acrosomal contents and plasma membrane.…”
Section: Calcium Oscillations In Sperm -A New Signalling System?mentioning
confidence: 99%